Educational Leadership in the Family Gender Equality Perspective in Surah An Nisa' verse 34 - Ma’arif, Samsul; Tamwifi, Irfan (EDUCATIO : Journal of Education, 2023)
In general, Muslims view that educational leadership in the family is a necessity based on QS. al Nisa': 34. In fact, in this verse, male leadership is followed for two reasons, because Allah has given advantages and because men provide for the family. The problem that arises is what if the husband only has advantages, but is unable to support the family, or vice versa? This study discusses the views of scholars regarding this matter. Apart from that, it reviews gender equality which is used as a perspective in reading about educational leadership in the family. Gender is a social construction of the roles of men and women. This role is unnatural. These roles are interchangeable between men and women. Some scholars argue that the husband's educational leadership in the family is based on QS. al-Nisa': 34 is not a necessity and is natural. The husband's leadership is ikhtiyari and kasby (sought after).